Digital Feminist Placemaking: The Case of the “Woman, Life, Freedom” Movement - Mehan, Asma (2024)
Throughout Iran and various countries, the recent calls of the “Zan, Zendegi, Azadi” (in Persian), “Jin, Jiyan, Azadi” (in Kurdish), or “Woman, Life, Freedom” (in English) movement call for change to acknowledge the importance of women. While these feminist protests and demonstrations have been met with brutality, systematic oppression, and internet blackouts within Iran, they have captured significant social media attention and coverage outside the country, especially among the Iranian diaspora and various international organizations. This article, grounded in feminist urban theories of the Global South, analyzes the digital feminist placemaking movement in Iran. As the first counter-revolution led by women, the movement utilizes digital art, graffiti, and protest movements to embody women’s solidarity groups and sympathy rallies. Our analysis employs various digital research methods, including social media scrutiny and the study of protest illustrations. Analyzing the digital feminist placemaking in Iran will enable us to compare the commonalities, differences, challenges, and opportunities between the minorities and majorities in the world’s countries. The outcomes of this research can help international organizations such as Amnesty International and the United Nations Agency for Gender Equality and Women’s Empowerment (UN Women), as well as policymakers, institutions, academics, and NGOs, to highlight the various ways in which broader public participation could be encouraged in the process of digital feminist insurgent placemaking.